REVIEWING FAMILY HISTORY: RECENT IRISH FICTION AND THE AVATARS OF MEMORY - STANCIU, Virgil (Studia Universitatis Babeș-Bolyai Philologia, 2018)
Reviewing Family History: Recent Irish Fiction and the Avatars of Memory. This article endeavours to demonstrate that in the fiction produced by writers of Irish origin towards the end of the 20th century a discernible feature is the renewed interest in history, this time not in the great historical upheavals that have always fascinated novelists and playwrights, but rather in the “little histories”of individuals and families. Sewn together, these patches of family history can be seen as being an unofficial (fictional?) biography of the nation. Rezumat. Revizuind istoria de familie: ficțiunea irlandeză recentă și avatarurile memoriei. Articolul de față încearcă să demonstreze faptul că una dintre trăsăturile detectabile în romanul irlanez al sfârșitului de veac XX este interesul reînnoit pentru istorie, de această dată nu atât în marile schimbări istorice care au fascinat întotdeauna romancieriii și dramaturgii, cât mai degrabă față de „micile istorii” despre indivizi și despre familii. Împletite împreună, aceste frânturi de istorii de familie, pot fi citite drept o biografie neoficială (ficțională?) a unei națiuni. Cuvinte cheie: biografie ficțională, trecutul imaginat, formă multi-stratificată